Autologous haematopoietic stem cell transplantation: a viable treatment option for CIDP. Issue 6 (21st November 2013) - Press, R; Askmark, H; Svenningsson, A; Andersen, O; Axelson, H W; Strömberg, U; Wahlin, A; Isaksson, C; Johansson, J-E J; Hägglund, H
Abstract : Objective: Only 70–80% of patients with chronic inflammatory demyelinating polyneuropathy (CIDP) respond satisfactorily to the established first-line immunomodulatory treatments. Autologous haematopoietic stem cell transplantation (AHSCT) has been performed as a last treatment resort in a few therapy-refractory cases with CIDP. We describe the results of AHSCT in 11 consecutive Swedish patients with therapy-refractory CIDP with a median follow-up time of 28 months. Method: Case data were gathered retrospectively for AHSCT treatments in 11 patients with CIDP refractory to the first-line immunomodulatory treatments, intravenous high-dose immunoglobulin, corticosteroids and plasma exchange and to one or more second-line treatments used in 10 of the 11 patients. Results: The median Inflammatory Neuropathy Cause and Treatment (INCAT) score within 1 month prior to AHSCT was 6 and the Rankin score 4. Total INCAT and Rankin scores improved significantly within 2–6 months after AHSCT and continued to do so at last follow-up. The motor action potential amplitudes (CMAP) improved already within 4 months (median) after AHSCT. Three of the 11 patients relapsed during the follow-up period, requiring retransplantation with AHSCT in one. Eight of the 11 patients maintained drug-free remission upon last follow-up. AHSCT was safe but on the short term associated with a risk of cytomegalovirus (CMV) and Epstein–Barr virus reactivation, CMV disease, haemorrhagic cystitis and pancreatitis. Conclusions: Our results though hampered by the limited number of patients and the lack of a control group suggest AHSCT to be efficacious in therapy-refractory CIDP, with a manageable complication profile. Confirmation of these results is necessary through randomised controlled trials.